Studies of injectable in situ depot-forming systems for drug delivery - Liu, Hui (2012)
In this project, injectable in situ depot-forming systems for drug delivery were studied. These systems are composed of a biodegradable polymer poly(D,L-lactide) (PLA) or poly(D,L-lactide-co-glycolide) (PLGA) and a low Mw model drug in an organic solvent. Polymer solution undergoes phase inversion when injected into an aqueous solution and forms depots in situ, with the drug trapped inside released over time. Several parameters were studied to understand their effects on the drug release dynamics, including polymer hydrophobicity and Mw, drug type and solvent type. These parameters also affect phase inversion dynamics, which was indirectly studied using solvent release kinetics and depot morphology. Furthermore, biocompatibility of the system was investigated. The results showed that some parameters, such as polymer hydrophobic property and high Mw as well as high affinity of solvent with water, lead to fast phase inversion and a high burst release; as the morphology of the depot formed is a porous solid. When polymers became hydrophilic or hydrophobic solvent was added into the formulation, phase inversion rate was slowed down, resulting in hollow depot structure formation; drug burst release was decreased. Through above studies, the drug release behavior in injectable in situ depot-forming systems can be better understood. The results of in vitro biocompatibility studies showed that DMSO was more biocompatible than NMP which was used in the commercial products. Based on the results from this work, we can make recommendations for reducing the high burst release and the toxicity of the organic solvent, which are two big problems in these systems.